2008
DOI: 10.1508/cytologia.73.259
|View full text |Cite
|
Sign up to set email alerts
|

Cell Proliferation of Diploid and Tetraploid H1 (ES) Cells in L15F10 Medium without Leukemia Inhibitory Factor

Abstract: SummaryMouse diploid and tetraploid H-1 (ES) cells cultured in L15F10 medium (2nH1 and 4nH1 cells, respectively) without leukemia inhibitory factor (LIF) (2nH1 (Ϫ) and 4nH1 (Ϫ) cells, respectively) were examined for their growth and cellular characteristics. Though the doubling times of 2nH1 (Ϫ) and 4nH1 (Ϫ) cells were longer than those of 2nH1 and 4nH1 cells, the phase fractions of 2nH1 (Ϫ) and 4nH1 (Ϫ) cells were the same as those of 2nH1 and 4nH1 cells, suggesting that occasional cell deaths occurred. DN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…It was reported that the DNA content of 4H1 (−) cells decayed gradually 15 . Decay and abrupt increase of DNA content of 4H1 (−) cells during long‐term culturing were observed in this study.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…It was reported that the DNA content of 4H1 (−) cells decayed gradually 15 . Decay and abrupt increase of DNA content of 4H1 (−) cells during long‐term culturing were observed in this study.…”
Section: Discussionsupporting
confidence: 61%
“…We reported that the pluripotency was maintained for several weeks in both diploid and tetraploid H1 cells in the medium without LIF 15 . The pluripotency disappeared in long‐term culturing for 2H1 (−) cells but not for 4H1 (−) cells in this study.…”
Section: Discussionmentioning
confidence: 47%